Restoring a Gray Partridge (Perdix perdix) Population and the Future of Predation Control - G. R. Potts (National Quail Symposium Proceedings, 2017)
For the past quarter century, the author’s partridge (Perdix perdix) population simulation model has been a useful guide, incorporating annual variation in chick survival rate, nesting habitat quality, nest predation, pesticides affecting the supply of insect food for the chicks and shooting. The 2 most important variables, density dependent nest predation and effect of insect food supply have been experimentally verified and all parts of the model have been extensively validated. However some very high densities achieved in northern France have not been fully explained. An ongoing conservation research project within the Sussex Downs Study (U.K.) area is described. The area is small (155 ha) but the numbers of partridges have increased ten-fold since 2003, with 57 per 100-ha in the autumn of 2005. Despite a very high density of pheasants no adverse effect of a caecal nematode (Heterakis gallinarum) has been detected. This project has been successful so far, but it has involved the removal of large numbers of meso-predators. Although legal, this predation control is unpopular and difficult. Moreover the smaller raptors are increasing and cannot be controlled. The question of whether the return of some top-predators could improve the situation for the partridge is explored by reference to experience in the USA and other countries. Few species have been studied more than the partridge yet, even more vigorous research will be necessary in future to meet the many challenges ahead.
Keywords: gray partridge; Perdix perdix; predation; predation control; UK